Audit Exemption For Small And Medium Enterprises: Perceptions Of Malaysian Auditors - Haron, Hasnah; Ismail, Ishak; Ganesan, Yuvaraj; Hamzah, Zulhawati (Asian Academy of Management (AAM), 2016)
The objective of the study is to examine audit frm size, the provision of non-audit services (NAS) and audit tenure as factors that inﬂuence the likelihood that an auditor agrees with allowing audit exemption. This study employs a 2 × 2 × 2 within-subject experimental design. Respondent auditors were required to evaluate 8 case scenarios. A total of 79 questionnaires were returned and used for data analysis. General Linear Measurement (Repeat Measure) was used to analyse the data. The study found that an audit frm size has a signifcant impact on the likelihood that an auditor agrees with oﬀering audit exemption. The larger the size of the frm, the greater is the likelihood of agreeing with allowing audit exemption. Therefore, it is suggested that small audit frms (with 5 or fewer employees) merge and focus on activities that contribute more added value such as consultancy. In so doing, auditors from these frms would be required to improve their knowledge and capacity by oﬀering these services and not merely focusing on traditional audit work for SMEs. This is because SMEs are known to have limited resources and capacity and thus would be expected to have poor internal control. The requirement of a mandatory audit for such frms might lead auditors to compromise their independence. Thus, the government